Optimalisasi Layanan Bimbingan dan Konseling dalam Pembentukan-Karakter Siswa-di Sekolah Dasar - Dela Ardianti; Wulandari Nurhazriyah; Suci Amali Amalia; Nadzifah Nurjanah Putria; Titi Sunarti (Jurnal Ilmu Sosial dan Humaniora, 2026)
Elementary education focuses not only on students' academic abilities but also on their overall development. Guidance and Counseling (BK) in elementary schools is crucial for helping students understand their potential, face challenges, and build strong character. Students receive support in their physical, cognitive, social, and emotional growth through BK services. This article examines relevant literature on how to maximize student development through BK services in elementary schools using descriptive qualitative methods. This research demonstrates that BK teachers help students develop, instill values and ethics, shape character, and help them face developmental challenges. To maximize BK services, teachers, parents, and schools must work together effectively. With the right support, BK services can significantly contribute to the holistic, independent, and future-ready growth of students.